Polyethylene flame-retardant master batch as well as preparation method and application thereof
By using bromine antimony composite flame retardant, antioxidant and anti-UV agent in polyethylene materials, polyethylene flame retardant masterbatches are prepared, which solves the problem of insufficient flammability and weather resistance of polyethylene materials in outdoor shielding supplies, and achieves excellent flame retardant and weather resistance of the material, and has good processing performance.
Patent Information
- Application Number
- CN202411323558.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The existing polyethylene materials have problems such as flammability, poor weather resistance and short service life in outdoor shielding products, and it is necessary to develop a polyethylene material with good flame retardancy and strong weather resistance.
The composite of bromine and antimony flame retardant is used as the flame retardant, combined with the composite of phosphite and hindered phenolic antioxidants, as well as the ultraviolet absorber and the hindered amine ultraviolet light stabilizer, polyethylene flame retardant masterbatches are prepared and processed through intensive refining and single screw extruder.
It achieves excellent flame retardant properties of polyethylene materials, meets the CPAI-84:1995 flame retardant standard, has short flame retardant time, and has good self-extinguishing properties of the material. At the same time, it improves the weather resistance of the material, has small color difference value after UV irradiation, and has high tensile strength retention rate; and has good processing performance, suitable for large-scale production.
Smart Images

Figure BDA0005054720780000051 
Figure BDA0005054720780000061 
Figure BDA0005054720780000062
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a polyethylene flame retardant masterbatch and a preparation method and application thereof. Background Art
[0002] Polyethylene (PE) has the advantages of being odorless, non-toxic, excellent in low temperature resistance, good chemical stability, resistance to most acids and alkalis, low water absorption, and excellent electrical insulation. It is widely used in chemical, agricultural, construction, packaging, and outdoor sheltering products.
[0003] Polyethylene has an oxygen index of about 17 and is flammable. When it is used in outdoor shelters (such as tents and awnings), it needs to be flame-retardant modified to avoid safety accidents such as fire. In addition, existing outdoor shelters based on polyethylene have the defects of poor weather resistance and short service life. It is of great significance to develop a polyethylene material with good flame retardancy and strong weather resistance to meet the application requirements of outdoor shelters. Summary of the invention
[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide a polyethylene flame retardant masterbatch; the second purpose of the present invention is to provide a method for preparing the polyethylene flame retardant masterbatch; the third purpose of the present invention is to provide a polyethylene material; the fourth purpose of the present invention is to provide a polyethylene flame retardant masterbatch, or the application of the polyethylene material.
[0005] The basic principle of the present invention is described as follows:
[0006] (1) The polyethylene flame retardant masterbatch provided by the present invention uses a compound of a bromine-based flame retardant and an antimony-based flame retardant as a flame retardant. The bromine-antimony compound can inhibit the continuation of the combustion reaction chain, reduce the combustion rate, and prevent the diffusion and propagation of the combustion products. Based on the bromine-antimony synergistic flame retardant mechanism, the polyethylene flame retardant masterbatch has excellent flame retardant properties.
[0007] (2) The polyethylene flame retardant masterbatch provided by the present invention uses a compound of a phosphite antioxidant and a hindered phenol antioxidant as an antioxidant. The phosphite antioxidant has a good antioxidant effect and can also provide color protection performance to prevent the polymer from yellowing or discoloring due to oxidative degradation; while the hindered phenol antioxidant can prevent the thermal oxidative degradation of the polymer material during the long-term aging process. Mixing the phosphite antioxidant with the hindered phenol antioxidant can provide an excellent antioxidant effect and improve the weather resistance of the material.
[0008] (3) The polyethylene flame retardant masterbatch provided by the present invention uses a compound of an ultraviolet light absorber and a hindered amine ultraviolet light stabilizer as an anti-UV agent. The ultraviolet light absorber has a greater protective effect on the polymer, helps to reduce color changes, delay yellowing and block the loss of physical properties, and can keep the physical properties of the material stable under ultraviolet light damage. The hindered amine ultraviolet light stabilizer helps to enhance the color fastness of the polyolefin material.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] The first aspect of the present invention provides a polyethylene flame retardant masterbatch, comprising the following raw materials: 25-35 parts of polyethylene resin, 60-70 parts of flame retardant, 3-5 parts of antioxidant, 3-5 parts of anti-UV agent, and 3-5 parts of lubricant;
[0011] The flame retardant includes a brominated flame retardant and an antimony flame retardant;
[0012] The antioxidants include phosphite antioxidants and hindered phenol antioxidants;
[0013] The anti-UV agent includes an ultraviolet light absorber and a hindered amine ultraviolet light stabilizer.
[0014] Preferably, the polyethylene flame retardant masterbatch comprises the following raw materials: 25-30 parts of polyethylene resin, 60-65 parts of flame retardant, 3-4 parts of antioxidant, 3-4 parts of anti-UV agent, and 4-5 parts of lubricant.
[0015] Preferably, the melt index of the polyethylene resin under the test condition of 190°C / 2.16kg is 15g / 10min-35g / 10min; further preferably, the melt index of the polyethylene resin under the test condition of 190°C / 2.16kg is 20g / 10min-30g / 10min. A polyethylene resin with a medium melt index (15g / 10min-35g / 10min, 190°C / 2.16kg) is selected as the resin matrix. This type of resin has good fluidity and dispersibility, can fully wrap various powders, ensure that the raw materials are evenly dispersed, and the resin has good elongation at break and high melt strength, and will not affect the elongation and coating effect of the overall product during cast extrusion.
[0016] Preferably, the polyethylene resin comprises linear low density polyethylene (LLDPE).
[0017] Preferably, the mass ratio of the brominated flame retardant to the antimony flame retardant is (2-4):1; further preferably, the mass ratio of the brominated flame retardant to the antimony flame retardant is (2.5-3.5):1.
[0018] Preferably, the brominated flame retardant includes ethylenebistetrabromophthalimide (RDT-5).
[0019] Preferably, the brominated flame retardant ethylenebistetrabromophthalimide (RDT-5) has a whiteness of ≥88, a particle size D50≤5μm, and a purity of ≥99%. In addition to flame retardancy, RDT-5 also has anti-ultraviolet radiation performance that other flame retardants do not have, and can simultaneously optimize the anti-ultraviolet performance of polyethylene flame retardant masterbatch, and the decomposition temperature of RDT-5 is greater than 300°C, and no decomposition occurs whether in the masterbatch production process or when used as a flame retardant masterbatch in cast extrusion.
[0020] Preferably, the antimony-based flame retardant includes at least one of antimony trioxide, antimony pentoxide, and sodium antimonate; further preferably, the antimony-based flame retardant is antimony trioxide.
[0021] Preferably, the antimony trioxide has a whiteness of ≥95, a particle size D50≤5 μm, and a purity of ≥99.5%. The decomposition temperature of antimony trioxide is greater than 300°C, and it does not decompose in the masterbatch production process or when used as a flame retardant masterbatch in cast extrusion.
[0022] Preferably, the mass ratio of the phosphite antioxidant to the hindered phenol antioxidant is (1-3):1; further preferably, the mass ratio of the phosphite antioxidant to the hindered phenol antioxidant is (1.5-2.5):1.
[0023] Preferably, the phosphite antioxidant includes at least one of bis(2,4-dicumylphenyl)pentaerythritol-diphosphite (antioxidant Revonox 608) and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate; further preferably, the phosphite antioxidant is antioxidant Revonox 608, which has a high phosphorus content (7.3wt%) and better antioxidant effect than other similar antioxidants. In addition, antioxidant Revonox 608 belongs to the category of secondary antioxidants, which can quench hydrogen peroxide during the self-oxidation process, thereby avoiding yellowing or discoloration of the polymer caused by oxidative degradation, and exhibits excellent color protection performance during the mixing process, which is something that other phosphite antioxidants cannot achieve even when added in excess.
[0024] Preferably, the hindered phenol antioxidant includes at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1010), 2,6-di-tert-butyl-p-methylphenol (BHT), and β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1076); further preferably, the hindered phenol antioxidant is antioxidant 1010. Antioxidant 1010 can effectively prevent thermal oxidative degradation of polymer materials during long-term aging, and is also a highly efficient processing stabilizer that can improve the discoloration resistance of polymer materials under high-temperature processing conditions.
[0025] Preferably, the mass ratio of the ultraviolet light absorber to the hindered amine ultraviolet light stabilizer is (1-2):1; further preferably, the mass ratio of the ultraviolet light absorber to the hindered amine ultraviolet light stabilizer is (1-1.5):1.
[0026] Preferably, the ultraviolet light absorber includes a benzophenone ultraviolet light absorber; further preferably, the ultraviolet light absorber includes UV-531. UV-531 has a greater protective effect on polymers, helps to reduce polymer color changes, and can also keep the physical properties of the material stable under ultraviolet light damage.
[0027] Preferably, the hindered amine UV light stabilizer includes at least one of UV-119 and UV-944; further preferably, the hindered amine UV light stabilizer is UV-119, which can enhance the color fastness of polyolefin materials, and UV-119 is neutral and will not react with flame retardants to affect flame retardant properties.
[0028] Preferably, the thermal decomposition temperature of the lubricant is greater than 350°C.
[0029] Preferably, the lubricant includes at least one of pentaerythritol stearate (PETS) and a bio-based wax powder lubricant; the bio-based wax powder lubricant includes Licocare RBW 102VITA wax (Clariant wax RBW102); further preferably, the lubricant is PETS. PETS as a lubricant can make the polyethylene flame retardant masterbatch have good demoulding and flow properties, make the flame retardant dispersed evenly, make the overall flowability of the flame retardant system better, and not easy to produce die accumulation. In addition, PETS has outstanding thermal stability, the thermal decomposition temperature is greater than 350°C, it is not easy to decompose during the processing, and can maintain the lubrication effect; PETS also has the effect of promoting nucleation of crystalline materials, and can significantly improve the transmittance and smoothness of the material.
[0030] Preferably, the melting point of the lubricant pentaerythritol stearate is ≥55°C.
[0031] The second aspect of the present invention provides a method for preparing the polyethylene flame retardant masterbatch according to the first aspect of the present invention, comprising the following steps:
[0032] The prepared raw materials are mixed, kneaded, extruded through a single screw extruder, and granulated to obtain the polyethylene flame retardant masterbatch.
[0033] Preferably, the extrusion temperature of the single screw extruder is 140-160°C; further preferably, the extrusion temperature of the single screw extruder is 145-155°C.
[0034] Preferably, the compression ratio of the screw is (34-38):1; further preferably, the compression ratio of the screw is (35-37):1.
[0035] When preparing polyethylene flame retardant masterbatch, an internal mixer is used for internal mixing, so that the flame retardant, antioxidant and anti-UV agent can be fully melted by the rotor in the internal mixer, the shear force in the processing process is small, and the flame retardant and other additives are not decomposed. Then, a single-screw extruder with small shear force and suitable for high filling ratio is selected for extrusion and hot cutting to obtain polyethylene flame retardant masterbatch.
[0036] The third aspect of the present invention provides a polyethylene material, comprising a polyethylene resin and the polyethylene flame retardant masterbatch described in the first aspect of the present invention.
[0037] Preferably, the mass ratio of the polyethylene flame retardant masterbatch to the polyethylene resin is 1:(8-12); further preferably, the mass ratio of the polyethylene flame retardant masterbatch to the polyethylene resin is 1:(9-11).
[0038] Preferably, the polyethylene resin includes at least one of high-density polyethylene (HDPE), low-density polyethylene (LDPE), and linear low-density polyethylene (LLDPE).
[0039] Preferably, the method for preparing the polyethylene material comprises the following steps:
[0040] The polyethylene flame retardant masterbatch is mixed with the polyethylene resin, and the mixture is subjected to cast extrusion or injection molding to obtain the polyethylene material.
[0041] Preferably, the polyethylene material includes at least one of polyethylene sheets, polyethylene plates, polyethylene strips and polyethylene films.
[0042] The fourth aspect of the present invention provides the polyethylene flame retardant masterbatch described in the first aspect of the present invention, or the use of the polyethylene material described in the third aspect in the fields of chemical industry, agriculture, construction, packaging, or in the preparation of outdoor shielding products.
[0043] Preferably, the outdoor sheltering products include tents and awnings.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] 1) The polyethylene flame retardant masterbatch provided by the present invention has excellent flame retardant properties. The polyethylene sheet prepared by compounding with polyethylene resin has flame retardant properties that meet the CPAI-84:1995 flame retardant standard, has a short ignition time, and has good self-extinguishing properties.
[0046] 2) The polyethylene flame retardant masterbatch provided by the present invention has good weather resistance. The polyethylene square plate prepared by compounding with the polyethylene resin is tested with reference to the ASTM G154 Cyclel standard, and the color difference value ΔE after 1000h of UV irradiation is <3.0; the polyethylene specimen prepared by compounding with the polyethylene resin is tested with reference to the standard ASTM D638-2019, and the tensile strength retention rate before and after UV irradiation is ≥90%, and the color and physical properties of the material are stable.
[0047] 3) The polyethylene flame retardant masterbatch provided by the present invention has excellent processing performance. During the process of compounding with polyethylene resin and casting extrusion to form polyethylene film, continuous production for 24 hours does not produce die accumulation and holes.
[0048] 4) The polyethylene flame retardant masterbatch provided by the present invention has a simple preparation method, mild process conditions, is easy to achieve large-scale production, and has high product quality and good quality stability.
[0049] 5) The polyethylene flame retardant masterbatch and polyethylene material provided by the present invention have both flame retardancy and weather resistance, and can meet the application requirements of chemical industry, agriculture, construction, packaging, or outdoor sheltering products such as tents and awnings. DETAILED DESCRIPTION
[0050] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.
[0051] Table 1 Raw material information of polyethylene flame retardant masterbatch in the examples and comparative examples
[0052]
[0053] Among them, the whiteness of RDT-5 is ≥88, the particle size D50≤5μm, and the purity is ≥99%; the whiteness of antimony trioxide is ≥95, the particle size D50≤5μm, and the purity is ≥99.5%; the melting point of the lubricant pentaerythritol stearate is ≥55°C.
[0054] Note: "Parts" in the following examples and comparative examples refer to "parts by mass" unless otherwise specified; the ratios between the compound components in the flame retardant, antioxidant and anti-UV agent refer to "mass ratio" unless otherwise specified.
[0055] Example 1
[0056] This embodiment provides a polyethylene flame retardant masterbatch, and the raw materials for preparation are shown in Table 2, wherein:
[0057] Flame retardant: RDT-5: antimony trioxide = 2.5:1;
[0058] Antioxidant: Revonox 608: Antioxidant 1010 = 2:1;
[0059] Anti-UV agent: UV-531:UV-119=1:1.
[0060] Table 2 Example 1 Polyethylene flame retardant masterbatch preparation raw materials
[0061]
[0062] The preparation method of polyethylene flame retardant masterbatch is:
[0063] The polyethylene resin, flame retardant, antioxidant, anti-UV agent and lubricant are mixed evenly in a mixing barrel, and kneaded in an internal mixer. The kneaded mixture is extruded in a single screw extruder (extrusion temperature 150°C, screw compression ratio 36:1), cut into particles by a hot cutting die, and sent into a large mixing barrel through a fan and a conveying pipeline to obtain polyethylene flame retardant masterbatch.
[0064] Example 2
[0065] This embodiment provides a polyethylene flame retardant masterbatch, and the raw materials for preparation are shown in Table 3, wherein:
[0066] Flame retardant: RDT-5: antimony trioxide = 3.5:1;
[0067] Antioxidant: Revonox 608: Antioxidant 1010 = 2:1;
[0068] Anti-UV agent: UV-531:UV-119=1:1.
[0069] Table 3 Example 2 Polyethylene flame retardant masterbatch preparation raw materials
[0070]
[0071]
[0072] The preparation method of polyethylene flame retardant masterbatch is:
[0073] The polyethylene resin, flame retardant, antioxidant, anti-UV agent and lubricant are mixed evenly in a mixing barrel, and kneaded in an internal mixer. The kneaded mixture is extruded in a single screw extruder (extrusion temperature 150°C, screw compression ratio 36:1), cut into particles by a hot cutting die, and sent into a large mixing barrel through a fan and a conveying pipeline to obtain polyethylene flame retardant masterbatch.
[0074] Comparative Example 1
[0075] This comparative example provides a polyethylene flame retardant masterbatch, which is different from Example 1 only in that the amount of the flame retardant is reduced to 55 parts, and the amount of the polyethylene resin is increased to 35 parts. The preparation process refers to Example 1-2.
[0076] Comparative Example 2
[0077] This comparative example provides a polyethylene flame retardant masterbatch, which is different from Example 1 only in that the flame retardant RDT-5:antimony trioxide = 2.5:1 is changed to decabromodiphenylethane:antimony trioxide = 2.5:1. The preparation process refers to Example 1-2.
[0078] Comparative Example 3
[0079] This comparative example provides a polyethylene flame retardant masterbatch, which is different from Example 2 only in that RDT-5:antimony trioxide = 3.5:1 is changed to octabromoether:antimony trioxide = 3.5:1. The preparation process refers to Example 1-2.
[0080] Comparative Example 4
[0081] This comparative example provides a polyethylene flame retardant masterbatch, which is different from Example 2 only in that RDT-5:antimony trioxide=3.5:1 is changed to RDT-5:antimony trioxide=1:1. The preparation process refers to Example 1-2.
[0082] Comparative Example 5
[0083] This comparative example provides a polyethylene flame retardant masterbatch, which is different from Example 1 only in that RDT-5:antimony trioxide = 2.5:1 is changed to RDT-55:antimony trioxide = 4.5:1. The preparation process refers to Example 1-2.
[0084] Comparative Example 6
[0085] This comparative example provides a polyethylene flame retardant masterbatch, which is different from Example 1 only in that 3 parts of Revonox 608: antioxidant 1010 = 2:1 is changed to 1 part of Revonox 608: antioxidant 1010 = 2:1. The preparation process refers to Example 1-2.
[0086] Comparative Example 7
[0087] This comparative example provides a polyethylene flame retardant masterbatch, which is different from Example 2 only in that 3 parts of Revonox 608: antioxidant 1010 = 2:1 is changed to 3 parts of antioxidant 168: antioxidant 1010 = 2:1. The preparation process refers to Example 1-2.
[0088] Comparative Example 8
[0089] This comparative example provides a polyethylene flame retardant masterbatch, which is different from Example 2 only in that 3 parts of UV-531:UV-119=1:1 is changed to 1 part of UV-531:UV-119=1:1. The preparation process refers to Example 1-2.
[0090] Comparative Example 9
[0091] This comparative example provides a polyethylene flame retardant masterbatch, which is different from Example 1 only in that 3 parts of UV-531:UV-119=1:1 is changed to 3 parts of UV-531. The preparation process refers to Example 1-2.
[0092] Comparative Example 10
[0093] This comparative example provides a polyethylene flame retardant masterbatch, which is different from Example 1 only in that 3 parts of UV-531:UV-119=1:1 is changed to 3 parts of UV-119. The preparation process refers to Example 1-2.
[0094] Comparative Example 11
[0095] This comparative example provides a polyethylene flame retardant masterbatch, which is different from Example 2 only in that 4 parts of lubricant PETS are replaced with 4 parts of lubricant EBS. The preparation process refers to Example 1-2.
[0096] Comparative Example 12
[0097] This comparative example provides a polyethylene flame retardant masterbatch, which is different from Example 1 only in that during the preparation process, the raw materials polyethylene resin, flame retardant, antioxidant, anti-UV agent, and lubricant are mixed evenly in a mixing barrel and then added to a twin-screw extruder for extrusion and granulation into polyethylene flame retardant masterbatch.
[0098] Comparative Example 13
[0099] This comparative example provides a polyethylene flame retardant masterbatch, which is different from Example 1 only in that 30 parts of LLDPE M2320 are replaced by 30 parts of LLDPE 7042. The preparation process refers to Example 1-2.
[0100] Performance Testing
[0101] 1. Flame retardant performance test
[0102] The polyethylene flame retardant masterbatch prepared in Example 1 and Comparative Examples 1, 2, 5, 6, 9, 10, 12, and 13 was mixed with polyethylene resin LDPE 2420H (CNOOC Shell, MI is 2g / 10min, tensile strength is 15MPa) at a mass ratio of 1:10, and extruded into 0.5mm thin sheets in a casting machine with a screw diameter of 35mm;
[0103] The polyethylene flame retardant masterbatch prepared in Example 2 and Comparative Examples 3, 4, 7, 8, and 11 was mixed with polyethylene resin HDPE F120A (Hanwha Total Petrochemical, MI is 0.04 g / 10 min, tensile strength is 22 MPa) at a mass ratio of 1:10, and extruded into 0.5 mm thin sheets in a casting machine with a screw diameter of 35 mm;
[0104] The obtained sheet was sampled and flame retardant tested according to the standard CPAI-84:1995 tent flame retardant test. The test results are shown in Table 4.
[0105] 2. Anti-UV test
[0106] The polyethylene flame retardant masterbatch prepared in Example 1 and Comparative Examples 1, 2, 5, 6, 9, 10, 12, and 13 was respectively mixed with polyethylene resin LDPE 2420H (CNOOC Shell, MI is 2g / 10min, tensile strength is 15MPa) at a mass ratio of 1:10, and injection molded into a square plate of 10mm*10mm*3mm (±0.5mm) on an injection molding machine;
[0107] The polyethylene flame retardant masterbatch prepared in Example 2 and Comparative Examples 3, 4, 7, 8, and 11 was mixed with polyethylene resin HDPE F120A (Hanwha Total Petrochemical, MI is 0.04 g / 10 min, tensile strength is 22 MPa) at a mass ratio of 1:10, and injection molded into a 10 mm*10 mm*3 mm (±0.5 mm) square plate on an injection molding machine;
[0108] The color difference value ΔE of the square plate was tested for 1000h according to the test standard of ASTM G154 Cycle 1. The test results are shown in Table 5.
[0109] 3. Tensile strength retention test
[0110] The polyethylene flame retardant masterbatch prepared in Example 1 and Comparative Examples 1, 2, 5, 6, 9, 10, 12, and 13 was respectively mixed with polyethylene resin LDPE 2420H (CNOOC Shell, MI is 2g / 10min, tensile strength is 15MPa) at a mass ratio of 1:10, and injection molded into 3.2mm thick strips on an injection molding machine;
[0111] The polyethylene flame retardant masterbatch prepared in Example 2 and Comparative Examples 3, 4, 7, 8, and 11 was mixed with polyethylene resin HDPE F120A (Hanwha Total Petrochemical, MI is 0.04 g / 10 min, tensile strength is 22 MPa) at a mass ratio of 1:10, and injection molded into 3.2 mm thick strips on an injection molding machine;
[0112] The tensile strength before and after UV irradiation was tested according to standard ASTM D638-2019, and the tensile strength retention rate was calculated. The tensile strength retention rate = tensile strength after UV irradiation / tensile strength before UV irradiation * 100%. The test results are shown in Table 6.
[0113] 4. Test of material accumulation at the die
[0114] The polyethylene flame retardant masterbatch prepared in Example 1 and Comparative Examples 1, 2, 5, 6, 9, 10, 12, and 13 was respectively mixed with polyethylene resin LDPE 2420H (CNOOC Shell, MI is 2g / 10min, tensile strength is 15MPa) at a mass ratio of 1:10, and the material accumulation at the lower end of the die was observed when the tent outer film was extruded and cast in a casting machine, and the time when the hole was generated was recorded;
[0115] The polyethylene flame retardant masterbatch prepared in Example 2 and Comparative Examples 3, 4, 7, 8, and 11 was mixed with polyethylene resin HDPEF120A (Hanwha Total Petrochemical, MI is 0.04g / 10min, tensile strength is 22MPa) at a mass ratio of 1:10, and the material accumulation at the lower end of the die was observed when the tent outer film was extruded and cast in a casting machine, and the time when the hole was generated was recorded. The test results are shown in Table 7.
[0116] Table 4 Flame retardant performance test results
[0117]
[0118]
[0119] Table 5 UV resistance test results
[0120] serial number Color difference ΔE after UV irradiation for 1000h serial number Color difference ΔE after UV irradiation for 1000h Example 1 2.75 Comparative Example 7 3.80 Example 2 2.90 Comparative Example 8 5.80 Comparative Example 1 2.87 Comparative Example 9 5.10 Comparative Example 2 4.50 Comparative Example 10 3.10 Comparative Example 3 8.90 Comparative Example 11 3.30 Comparative Example 4 2.70 Comparative Example 12 / Comparative Example 5 3.25 Comparative Example 13 3.50 Comparative Example 6 4.30
[0121] Table 6 Tensile strength retention test results
[0122]
[0123]
[0124] Table 7 Test results of die material accumulation
[0125] serial number Material accumulation at the bottom of the die during 24-hour continuous production Continuous production for 24 hours to produce holes Example 1 No obvious accumulation No holes Example 2 No obvious accumulation No holes Comparative Example 1 No obvious accumulation No holes Comparative Example 2 Material accumulation began to appear after 1 hour Holes started to appear at 2h Comparative Example 3 The die material is severely burnt Too many holes, unable to produce normally Comparative Example 4 No obvious accumulation Holes started to appear after 14 hours Comparative Example 5 No obvious accumulation No holes Comparative Example 6 Material accumulation began to occur after 3 hours of production Holes started to appear after 5 hours Comparative Example 7 Material accumulation began to occur after 6 hours of production Holes began to appear after 8 hours Comparative Example 8 No obvious accumulation No holes Comparative Example 9 No obvious accumulation No holes Comparative Example 10 No obvious accumulation No holes Comparative Example 11 Material accumulation began to occur after 12 hours of production Holes began to appear after 13 hours Comparative Example 12 / / Comparative Example 13 Material accumulation began to occur after 6 hours of production Holes began to appear after 7 hours
[0126] Table 4 is the flame retardant performance test results, Table 5 is the UV resistance test results, Table 6 is the tensile strength retention test results, and Table 7 is the die buildup test results. It can be seen from Tables 4-7 that:
[0127] (1) In Examples 1 and 2, polyethylene resin LLDPE M2320 with a medium melt index (20 g / 10 min, 190° C. / 2.16 kg) and good fluidity and dispersibility, a flame retardant compound of RDT-5 and antimony trioxide in a mass ratio of (2.5-3.5):1, an antioxidant Revonox 608 and an antioxidant 1010 in a mass ratio of (1.5-2.5):1, an ultraviolet light absorber UV-531 and a hindered amine ultraviolet light stabilizer UV-119 in a mass ratio of (1-1.5):1, and a PETS lubricant are used as raw materials, mixed and kneaded, and extruded using a single screw extruder to obtain a polyethylene flame retardant masterbatch having excellent flame retardant properties. After being diluted in proportion, the material can pass the flame retardant test of CPAI-84:1995, and the material has a short flame delay time and good self-extinguishing property. Based on the combined effect of the antioxidant and the UV inhibitor, the material is oxidized to a temperature of 100 ° C. in accordance with ASTM G154. The color difference value ΔE of UV irradiation for 1000h measured by the test standard of Cycle1 is maintained in the range of 2.75-2.90, the color difference value is small, and the tensile strength retention rate before and after UV irradiation is ≥90.0%, that is, the color and physical properties of the material change little, and the polyethylene flame retardant masterbatch can provide excellent weather resistance; during the extrusion casting process, there is no obvious accumulation of material and no holes at the lower end of the die for continuous production for 24h, and the processing performance is good. It can be seen that ensuring that the types and proportions of the raw materials for the preparation of the polyethylene flame retardant masterbatch are within the scope provided by the present invention can make the polyethylene material containing the polyethylene flame retardant masterbatch and the polyethylene resin have excellent flame retardancy, weather resistance and processing performance, and can meet the application requirements in the fields of outdoor shielding products.
[0128] (2) The only difference between Comparative Example 1 and Example 1 is that the amount of flame retardant used is reduced, but the flame retardant masterbatch in Comparative Example 1 has a flammability delay time of more than 4 seconds for the polyethylene sheet, and the flame retardant performance test fails. Moreover, the tensile strength retention rate of the corresponding strips is reduced after UV irradiation.
[0129] (3) The difference between Comparative Example 2 and Example 1 is that decabromodiphenylethane replaces RDT-5, and the difference between Comparative Example 3 and Example 2 is that octabromoether replaces RDT-5. The color difference value ΔE of the polyethylene square plate corresponding to the flame retardant masterbatch in Comparative Example 2 after UV irradiation for 1000 hours increases to 4.50, and the tensile strength retention rate of the polyethylene strip before and after UV irradiation decreases to 69.2%. During the extrusion casting process of polyethylene film production, material accumulation begins to appear after 1 hour of continuous production and holes begin to appear after 2 hours; the color difference value ΔE of the polyethylene square plate corresponding to the flame retardant masterbatch in Comparative Example 3 after UV irradiation for 1000 hours increases to 8.90, and the tensile strength retention rate of the polyethylene strip before and after UV irradiation decreases to 72.2%. During the extrusion casting process of polyethylene film production, the die accumulation is severely scorched and has many holes during continuous production, and normal production cannot be achieved. The results show that the dispersibility of decabromodiphenylethane and octabromoether is not as good as that of RDT-5, which can easily lead to a decrease in flame retardancy. In addition, their heat resistance is also lower than that of RDT-5. During cast extrusion, flame retardants are easily decomposed, resulting in holes. Among them, octabromoether has the worst heat resistance, and the time for material accumulation and holes to occur is short.
[0130] (4) The difference between Example 5 and Example 1 is that the mass ratio of flame retardant RDT-5 to antimony trioxide is changed from 2.5:1 to 4.5:1, and the difference between Example 4 and Example 2 is that the mass ratio of flame retardant RDT-5 to antimony trioxide is changed from 3.5:1 to 1:1. The mass ratios of flame retardants in both examples are not within the scope provided by the present invention. The burning length of the polyethylene sheet corresponding to the flame retardant masterbatch in Example 5 exceeds the standard, and the ignition time of the polyethylene sheet corresponding to the flame retardant masterbatch in Example 4 exceeds 4s, and the flame retardant performance test results are unqualified; in addition, the tensile strength retention rates of the polyethylene strips corresponding to the flame retardant masterbatch in Example 5 and Example 4 before and after ultraviolet irradiation are reduced to 85.7% and 72.2%, respectively; and when the flame retardant masterbatch in Example 4 is used in the production of polyethylene film, holes begin to appear after 14 hours of continuous extrusion casting production. It shows that when the mass ratio of RDT-5 to antimony trioxide is not within the range provided by the present invention, the bromine antimony ratio is unbalanced, the flame retardant efficiency is reduced, and the antimony trioxide ratio increases, which is prone to agglomeration, resulting in large white spots during cast extrusion and easy holes after stretching.
[0131] (5) The difference between Comparative Example 6 and Example 1 is that the amount of antioxidant used is reduced, and the difference between Comparative Example 7 and Example 2 is that antioxidant 168 is used to replace antioxidant Revonox 608. It can be seen that the color difference value ΔE of the polyethylene square plate corresponding to the flame retardant masterbatch in Comparative Examples 6 and 7 after UV irradiation for 1000 hours is increased, and the tensile strength retention rate of the corresponding sample strips before and after UV irradiation is reduced. In addition, when the flame retardant masterbatch in Comparative Example 6 is used for polyethylene film production, material accumulation begins to occur after 3 hours of continuous extrusion casting production, and holes begin to appear after 5 hours. When the flame retardant masterbatch in Comparative Example 7 is used for film production, material accumulation begins to occur after 6 hours, and holes begin to appear after 8 hours. This shows that insufficient amount of antioxidant or failure to use antioxidant Revonox 608 with a high phosphorus content will lead to poor weather resistance of the flame retardant masterbatch; and when the proportion of high temperature resistant antioxidant Revonox 608 is reduced, the ability to extract free radicals generated by high temperature processing becomes weaker, thereby weakening the processing protection effect, and it is easy to produce material accumulation and holes.
[0132] (6) The only difference between Comparative Example 9 and Example 1 is that the hindered amine UV stabilizer UV-119 is not added, the only difference between Comparative Example 10 and Example 1 is that the UV absorber UV-531 is not added, and the only difference between Comparative Example 8 and Example 2 is that the amount of anti-UV agent is reduced. It can be seen that compared with Examples 1 and 2, changing the amount or type of the compound anti-UV agent will result in the inability to fully exert the synergistic effect of UV-531 (physical property protection) and UV-119 (color protection), resulting in a decrease in the weather resistance of the material.
[0133] (7) The only difference between Comparative Example 11 and Example 2 is that EBS is used instead of PETS as the lubricant. Since the dispersibility and heat resistance of EBS are worse than those of PETS, when the flame retardant masterbatch in Comparative Example 11 is used in the production of polyethylene film, material accumulation begins to occur after 12 hours of continuous extrusion casting production, and holes begin to appear after 13 hours, resulting in poor processing performance.
[0134] (8) The only difference between Comparative Example 12 and Example 1 is that the raw materials are not mixed and kneaded during the preparation process and a twin-screw extruder is used for extrusion granulation. Since the twin-screw extruder is not suitable for the production of high filling ratios, the masterbatch production process is not smooth, the material strips are brittle, and cannot be smoothly drawn.
[0135] (9) The only difference between Comparative Example 13 and Example 1 is that polyethylene resin LLDPE 7042 is used instead of polyethylene resin LLDPE M2320. LLDPE 7042 has poor fluidity and poor dispersibility of flame retardants, resulting in the flame retardant masterbatch in Comparative Example 13 corresponding to the polyethylene sheet ignition time exceeding 4 seconds, and the flame retardant performance of the flame retardant masterbatch is reduced. When used in the production of polyethylene film, material accumulation begins to occur after 6 hours of continuous extrusion casting production, and holes begin to appear after 7 hours, and the processing performance deteriorates.
[0136] The polyethylene flame retardant masterbatch provided by the present invention selects linear low-density polyethylene with a medium melt index (15g / 10min-35g / 10min, 190°C / 2.16kg) as a resin matrix, adds a composite flame retardant with a balanced bromine-antimony ratio, and then matches an antioxidant, an anti-UV agent and a high-temperature resistant lubricant in a suitable ratio, and uses a mixer for internal mixing and then uses a single screw for extrusion and hot cutting into pellets. Based on the mutual coordination of raw material components, ratios and process conditions, the polyethylene flame retardant masterbatch has excellent flame retardancy, weather resistance and good processing performance, and the polyethylene material containing the polyethylene flame retardant masterbatch also has both flame retardancy and weather resistance, and can meet the application requirements of outdoor shielding products and other fields.
Claims
1. A polyethylene flame retardant masterbatch, characterized in that: The preparation raw materials include the following by weight: 25-35 parts of polyethylene resin, 60-70 parts of flame retardant, 3-5 parts of antioxidant, 3-5 parts of anti-UV agent, and 3-5 parts of lubricant; The flame retardant includes a brominated flame retardant and an antimony flame retardant; The antioxidants include phosphite antioxidants and hindered phenol antioxidants; The anti-UV agent includes an ultraviolet light absorber and a hindered amine ultraviolet light stabilizer.
2. The polyethylene flame retardant masterbatch according to claim 1, characterized in that: The polyethylene resin has a melt index of 15 g / 10 min to 35 g / 10 min under the test condition of 190° C. / 2.16 kg; Preferably, the polyethylene resin comprises linear low density polyethylene.
3. The polyethylene flame retardant masterbatch according to claim 1, characterized in that: The mass ratio of the brominated flame retardant to the antimony flame retardant is (2-4):1; Preferably, the brominated flame retardant comprises ethylenebistetrabromophthalimide; Preferably, the antimony-based flame retardant includes at least one of antimony trioxide, antimony pentoxide and sodium antimonate.
4. The polyethylene flame retardant masterbatch according to claim 1, characterized in that: The mass ratio of the phosphite antioxidant to the hindered phenol antioxidant is (1-3):1; Preferably, the phosphite antioxidant includes at least one of bis(2,4-dicumylphenyl)pentaerythritol-diphosphite and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate; Preferably, the hindered phenol antioxidant includes at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,6-di-tert-butyl-p-methylphenol, and n-octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.
5. The polyethylene flame retardant masterbatch according to claim 1, characterized in that: The mass ratio of the ultraviolet light absorber to the hindered amine ultraviolet light stabilizer is (1-2):1; Preferably, the ultraviolet light absorber comprises a benzophenone ultraviolet light absorber; Preferably, the hindered amine ultraviolet light stabilizer includes at least one of UV-119 and UV-944.
6. The polyethylene flame retardant masterbatch according to claim 1, characterized in that: The thermal decomposition temperature of the lubricant is greater than 350°C; Preferably, the lubricant includes at least one of pentaerythritol stearate and bio-based wax powder lubricant.
7. The method for preparing the polyethylene flame retardant masterbatch according to any one of claims 1 to 6, characterized in that: The following steps are involved: The prepared raw materials are mixed, kneaded, extruded through a single screw extruder, and granulated to obtain the polyethylene flame retardant masterbatch.
8. A polyethylene material, characterized in that: It comprises polyethylene resin and the polyethylene flame retardant masterbatch according to any one of claims 1 to 6.
9. The polyethylene material according to claim 8, characterized in that The mass ratio of the polyethylene flame retardant masterbatch to the polyethylene resin is 1:(8-12).
10. Use of the polyethylene flame retardant masterbatch according to any one of claims 1 to 6, or the polyethylene material according to any one of claims 8 to 9 in the fields of chemical industry, agriculture, construction, packaging, or in the preparation of outdoor shielding products.
Citation Information
Patent Citations
Flame-retardant master batch for weather-resistant polyethylene as well as preparation method and application thereof
CN108034117A
Color master batch for membranes and preparation method of color master batch
CN110305391A
Functional additive composite master batch and preparation method and application thereof
CN112280159A
High-concentration engineering plastic flame-retardant master batch and preparation method thereof
CN113265109A
Flame retardant masterbatch and its production
JP1996109269A
Cited By
Flame-retardant nylon composition as well as preparation method and application thereof
CN121379143A